1963
DOI: 10.1017/s000748530004904x
|View full text |Cite
|
Sign up to set email alerts
|

The ecology of the mosquitos of the Northern Guinea Savannah of Nigeria

Abstract: The ecology of the adult mosquitos of the Northern Guinea Savannah was studied from 1960 to 1962 in the Kaduna area mainly in two Hausa villages, Anguwun Rimi and Kangimi, and in nearby Fulani settlements. A description of the area and various types of village huts is given together with an account of the climate and meteorological data. Emphasis was on the Anophelines and their relation to malaria but at the same time information on the Culicines is presented.Biting catches, in which mosquito scouts acting as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
56
2

Year Published

1978
1978
2008
2008

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 63 publications
(62 citation statements)
references
References 20 publications
3
56
2
Order By: Relevance
“…Hamon (1964) also reported that in Mauritania most of the mosquitoes that entered bait-nets in the early part of the night left before sunrise. In Nigeria more adults of Anopheles gambiae and Anopheles nili were caught in direct bait catches on man than in bed-net collections irrespective of whether the catches were performed in village huts or outside in the compounds (Service, 1963). There was no significant difference between the numbers of Anopheles Junestus caught by the two methods.…”
Section: Limitations Of Bed-nets For Human and Animal Baitsmentioning
confidence: 82%
See 4 more Smart Citations
“…Hamon (1964) also reported that in Mauritania most of the mosquitoes that entered bait-nets in the early part of the night left before sunrise. In Nigeria more adults of Anopheles gambiae and Anopheles nili were caught in direct bait catches on man than in bed-net collections irrespective of whether the catches were performed in village huts or outside in the compounds (Service, 1963). There was no significant difference between the numbers of Anopheles Junestus caught by the two methods.…”
Section: Limitations Of Bed-nets For Human and Animal Baitsmentioning
confidence: 82%
“…5.7a). Sometimes one or more sides of the net are partly rolled up and pinned or tucked into place (Sasa & Sabin, 1950;Service, 1963), or a horizontal slit made (Davidson, 1949). Alternatively, the entire net can be raised a few inches from the ground (Akiyama, 1973;Hamon, 1964;Laarman, 1958) to give access to hungry mosquitoes (Fig.…”
Section: Bed-netsmentioning
confidence: 99%
See 3 more Smart Citations